Salt dependence and thermodynamic interpretation of the thermal denaturation of small DNA restriction fragments. - Hillen, W (1981)
The influence of cation concentration on the thermal denaturation of DNA restriction fragments from the E. coli lac regulatory region and from pVH51, ranging in size from 43- to 880- bp, is described. Upon increasing the ionic strength, the melting transitions broaden in a cooperative manner at salt concentrations characteristic for the specific fragment. For three fragments studied in detail, the salt concentration dependence at the midpoint varied between 0.03 and 0.19 M Na+. Along with the broadening, the melting transitions become more symmetrical. This result is discussed with respect to the irreversibility of melting transitions at low ionic strength. After a cooperative broadening, the shape of the melting curves remains constant up to salt concentrations of 0.5 M Na+. The dTM/dlog[Na+] values for three fragments fall between 15.7 and 16.7. An easily applicable approximation of the van't Hoff equation is used to evaluate the enthalpies of 13 transitions arising from the denaturation of 43 to 600 bp. The results of this analysis are compared to calculations of the expected enthalpies based on calorimetric measurements. The TMs of most transitions were directly related to the base composition, but several deviations from the predicted behavior were observed. The possible influences of fragment length and sequence on the thermal stability are discussed. The experimental and mathematical procedure to resolve a thermal denaturation transition with a width f 0.17 +/- 0.01 degrees and its distinction from another preceeding transition only approximately 0.15 degrees away in an 880-bp Hae III fragment from pVH51 is described. This transition is about half as wide as the smallest one reported to date.